2021
DOI: 10.1111/jpn.13491
|View full text |Cite
|
Sign up to set email alerts
|

Effects and interaction of dietary electrolyte balance and citric acid on growth performance, intestinal histomorphology, digestive enzyme activity and nutrient transporters expression of weaned piglets

Abstract: Fifty‐six piglets were weaned at 21 days and randomly assigned to 1 of 8 dietary treatments with 7 replicate pens for a 14‐day experimental period. The eight experimental diets were prepared via a 2 × 4 factorial arrangement with citric acid (CA; 0 and 0.3%) and dietary electrolyte balance (dEB, Na +K − Cl mEq/kg of the diet; −50, 100, 250, and 400 mEq/kg). Varying dEB values were obtained by altering calcium chloride and sodium bicarbonate contents. Dietary CA significantly increased (p < .05) villus height (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The structure and function of the intestine are reflected through the morphology of the intestine ( Moeser et al., 2007 ; Stokes, 2017 ). In the current experiment, it was found that the ME diet improved the morphological and structural integrity of the duodenum and jejunum in piglets compared to the LE diet and the HE diet, which was consistent with previous studies ( Deng et al., 2021 ). The regression results showed that the dEB corresponding to the highest villous height and V:C of duodenum and jejunum were 243.06, 255.95, 255.82 and 264.2 mEq/kg, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The structure and function of the intestine are reflected through the morphology of the intestine ( Moeser et al., 2007 ; Stokes, 2017 ). In the current experiment, it was found that the ME diet improved the morphological and structural integrity of the duodenum and jejunum in piglets compared to the LE diet and the HE diet, which was consistent with previous studies ( Deng et al., 2021 ). The regression results showed that the dEB corresponding to the highest villous height and V:C of duodenum and jejunum were 243.06, 255.95, 255.82 and 264.2 mEq/kg, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The jejunal tissue was removed and fixed in a 4% paraformaldehyde solution, then the fixed tissue was paraffin-embedded, and the jejunal tissue block was cut approximately 4-μm thick using a microtome and stained with hematoxylin and eosin (H&E) ( 26 ). The villus height was the distance from the villus tip to the crypt mouth, and crypt depth was the distance from the crypt mouth to the base of the crypt ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chick jejunal and ileal samples were subjected to overnight fixation using 10% neutral formaldehyde, followed by dehydration, pruning, embedding, sectioning, staining, and tablet sealing for microscopic examination ( Deng et al, 2021 ). Later, the digital trim camera microscope (BA210 Digital, Motic) was utilized for section observation; meanwhile, the image analysis software (Motic Images Advanced 3.2) was employed for measuring and analyzing villus length, crypt depth, and intestinal wall of jejunal and ileal samples.…”
Section: Methodsmentioning
confidence: 99%